The Nature Of Fasting - Ibn Taymiyyah, Shaykh Al-Islam Taqiuddin Abdul-Halim (Lahore Darussalam, 2000)
This book will help the reader better understand the fine points about fasting. What is the nature of the things that break the fast? What are the rules by which one can know the difference between what breaks the fast and what does not? These question are more answered by Shaykh Al-Islam Ibn Taymiyyah in his discussion of the Nature of Fasting. Publishers Note All praise is due to Allah, and may He grant peace and blessings upon His Last Messenger Muhammad. This is a translation one of the smaller publications from the works of Shaykh Al-Islam Taqiuddin Ahmad bin 'Abdul-Halim Ibn Taymiyyah. It has been published in this form a variety of times with a number of minor additions to the text under the title, ""Hagigatus-Siyam,"" or, ""The Nature of Fasting."" We have revised our version to meet the source section of Majmu' AI-Fatawa (25:219) from where it appears that the original booklet - with the exception of the questions, of which most appear on earlier pages - has been taken. We have inserted brackets to signify the additions, which earlier publishers probably took from other sections of his writings. We have also added brief references to the text for the Hadiths. I would like to express gratitude to brother Ebrahim Aly Ma'rouf for the original translation of this booklet, and the Darussalam staff for their editing and layout work. In the end all praise is due to Allah, and upon Him we depend. Abdul-Malik Mujahid, General Manager, Darussalam Table of Contents THE NATURE OF THINGS THAT BREAK THE FAST THE NATURE OF THINGS THAT DO NOT BREAK THE FAST Questions and Answers Fasting the Cloudy Day and the Day of Doubt Fasting and Shortening the Prayer for the Traveler Fasting for the Traveler: Better or Worse? Must One Intend to Fast the Night Before? Is the Intention Necessary Every Day? How Fast is the Fast to be Broken? Eating After the Earlier Adhan If Fasting Causes Fainting and Madness The Case of A Pregnant Woman.
Keywords: Fasting--Religious aspects--Islam